Maternal exposure to organochlorine pesticides in Western Australia - Reid, Alison; Callan, A.; Stasinska, A.; Heyworth, J.; Phi, D.; Odland, J.; Hinwood, A. (2013)
Background: Organochlorine pesticides (OCPs) persist over long periods of time. Little is known about levels of OCPs in the plasma of non smoking pregnant women in Western Australia. The aim of this study was to (1) determine exposure concentrations in a sample of pregnant women in Western Australia; (2) to determine the significant environmental, lifestyle and activity contributors to maternal exposure concentrations of OCPs and (3) to compare the measured maternal exposure concentrations with those measured in other countries. Methods: In a cross-sectional survey, 167 pregnant women located in rural and urban Western Australia provided plasma and answered questionnaires seeking information on lifestyle, demographics and the determinants of exposure to OCPs. Results: Of the 10 OCPs examined only HCB, ß-HCH and p,p'DDE had concentrations above the limit of detection for more than 50% of samples. The mean level of HCB was 0.08. µg/L (range 0.005-2.0. µg/L), ß-HCH 0.18. µg/L (range 0.04-3.16. µg/L) and p,p'DDE 1.05. µg/L, (range 0.03-17.04. µg/L). HCB concentrations were higher in women who ate seafood during pregnancy and who were older and lower among those with a history of breastfeeding. Concentrations of ß-HCH were higher among women with a household income <$80,000 and lower among those with a history of breastfeeding. Concentrations of p,p'DDE were higher among women who lived within 1. km of industry and lower among those with a history of breastfeeding. Conclusions: Concentrations of pesticides were low in Western Australian mothers compared with international studies. © 2013 Elsevier B.V..